Peningkatan Kesadaran Masyarakat Dalam Hal Pemasaran Digital, Kebersihan Lingkungan, Serta Pentingnya Kesehatan Keluarga - Asep Saeful Falah; Siti Hodijah; Mahesa Anabrang Widianto; Anisya Fadilah Aini; Muhammad Farhan; Akram Badruttaman Mustagfirin; Putri Ira Agustin; Mina Nurmalasari; Hilman Mulyana; Tengku Muhammad; Dede Piki Lesmana (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
The Thematic Community Service Program (KKNT) in Bangbayang Village, conducted by STIE Latifah Mubarokiyah students, has run smoothly and has had a positive impact on both students and the village community. Through various activities, such as observing MSMEs, conducting digital marketing seminars, conducting a waste management program using rocket stoves and waste decomposition signs, and participating in integrated health posts (Posyandu) and community outreach activities, students have been able to apply the knowledge they gained in class to real-world practice in the community. These activities not only broaden students' knowledge and experience but also contribute significantly to increasing public awareness of digital marketing, environmental cleanliness, and the importance of family health. Thus, this KKNT serves as a valuable platform for community service and strengthens the relationship between students and the Bangbayang Village community.